2015
DOI: 10.6018/analesps.31.3.176981
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral engagement and disaffection in school activities: Exploring a model of motivational facilitators and performance outcomes

Abstract: Previous research has shown that perceived control, task value, behavioral engagement and disaffection are personal determinants of academic performance. However, little research has simultaneously examined these constructs in secondary education. The present study analyzed the structural relationships between these variables and the role of engagement and disaffection as mediators of control and value on performance. Participants were 446 students (51.3% girls) ranging in age from 12 to 16 years attending six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 48 publications
0
10
0
1
Order By: Relevance
“…Academic engagement has been conceptualized as the extent to which students are committed to school and motivated to learn ( González et al, 2015 ). The engagement concept has been traditionally applied in the work area, and is understood in terms of task behavior, effort, persistence, participation and work habits ( Schaufeli et al, 2002a , b ; Kahu, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Academic engagement has been conceptualized as the extent to which students are committed to school and motivated to learn ( González et al, 2015 ). The engagement concept has been traditionally applied in the work area, and is understood in terms of task behavior, effort, persistence, participation and work habits ( Schaufeli et al, 2002a , b ; Kahu, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…The engagement concept has been traditionally applied in the work area, and is understood in terms of task behavior, effort, persistence, participation and work habits ( Schaufeli et al, 2002a , b ; Kahu, 2013 ). However, in the last years, this construct has become increasingly complex with the advent of new instruments that define AE in terms of three dimensions: behavioral (i.e., time on task), emotional (i.e., interest and value), and cognitive engagement (i.e., self-regulation and learning strategies; Fredricks et al, 2004 ; González et al, 2015 ). Recent research has suggested a fourth dimension of student’s engagement in school, namely personal agency, which conceptualizes students as proactive, as agents of action by showing initiative, interest and making suggestions ( Veiga et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…En cuanto al primer objetivo específico, referido a la descripción de los tipos de comportamiento disóciales que ocurren en los estudiantes de educación secundaria de la Unidad Educativa "Alto Barinas Norte"; se logró observar y registrar para su clasificación, un conjunto de manifestaciones conductuales caracterizados por la presencia de la agresión verbal y física, delincuencia, burlas e incumplimiento de las normas de convivencia, que en conjunto afectaban el bienestar estudiantil. Estos hechos fueron identificados como evidencias de trastorno disocial, frente a los cuales los docentes no actuaban de manera proactiva, siendo común que obviaran lo ocurrido o adoptasen una actitud complaciente, producto del desconocimiento de estrategias para actuar en tales situaciones o no contar con competencias para ello (González, et al, 2015).…”
Section: Resultados Y Discusiónunclassified
“…Utility value is associated with the perceived usefulness of the task in achieving personal goals. Utility and attainment values have been found to influence academic engagement in secondary school students (González, Paoloni, Donolo, & Rinaudo, 2015;Watt et al, 2012). Fewer differences in mathematics attainment and utility value between girls and boys have been reported than is the case with intrinsic value (Watt, 2004;Watt et al, 2012).…”
Section: Introductionmentioning
confidence: 99%